Paradoxes conceptuels du développement durable et nouvelles initiatives de coopération Nord-Sud : le Mécanisme pour un Développement Propre (MDP) - Moïse Tsayem Demaze (Cybergeo, 2009)
Retrospective and prospective reading of the texts that found sustainable development, particularly the Brundtland report, makes it possible to recall the genesis of this concept and to analyze its theoretical bases. This reading reveals that sustainable development, such as it was conceived and diffused by UNO, contains many conceptual paradoxes which are due to a positive vision of the interrelationships between economic growth, social equity and safeguarding of the environment. However, the positive and the integrative characteristics of these relations are not always obvious. The difficult implementation of sustainable development however generates new initiatives of co-operation, like the Clean Development Mechanism (CDM). It associates developed and developing countries within the framework of the Kyoto protocol whose first application phase goes from 2008 to 2012. A quantitative assessment of this mechanism at August 10, 2008, shows that 1136 projects are validated. They represent a commercial volume of 220 million tons of equivalent CO2 per annum, avoided or saved in developing countries in various activities such as energy industries and waste processing. Developed countries which take great parts in the CDM by financial and technological investments are United Kingdom (38% of the projects) and Switzerland (23% of the projects). India (31% of the projects) and China (22% of the projects) are developing countries most implied in this new mechanism. The propagation of projects illustrates the importance of economic instruments in the implementation of sustainable development at international level.